MOTIVASI, KEMAMPUAN, PENGALAMAN, KETERLIBATAN, KEDISIPLINAN SEBAGAI FAKTOR INTERNAL KARYAWAN DAN PEMBENTUKAN KINERJA KARYAWAN - Didit Darmawan (Universitas Mahendradatta Denpasar, 2022)
A The success of a company to be able to achieve a good level of performance is certainly influenced by internal and external factors of human resources with different levels. Every company has the hope to achieve the optimization of the work of employees and to achieve effectiveness and efficiency in accordance with organizational goals. This study will observe motivation, ability, experience, involvement, discipline as internal factors of employees. Furthermore, it is analyzed and determined the role of each of these internal factors on employee performance. The sample is set as many as 100 respondents taken from employees in the production department as operators. The analysis tool is multiple linear regression analysis. From the results of the study, it is evident that the variables of motivation, ability, experience, involvement and discipline have a significant influence partially or simultaneously on employee performance.